(untitled) (Research, Society and Development, 2019)
In this article we present notes from a dissertation of the first author, Our objective is to discuss an analysis of teaching actions related to the teaching of robotics, which has been developed through an educational project in a classroom last year of "elementary school I". The survey of data was done in a school hall in São Bernardo do Campo, through semi-structured interviews carried out with the teachers, photographic records and observation of lessons. The results highlighted the protagonist role of the teachers to plan, organize and develop activities and, also, revealed that the interventions carried out by teachers challenged students and raising chances, test strategies and find solutions for the most varied situations that were appearing during the construction of the toys in educational Robotics together with contents of science.